OPTIMIZATION DESIGN OF THE INDEPENDENT WHEEL AXLE-AXLE BASED ON OSF AND RSM - YE Shuang; LIU Qiang; HUANG KunLan; FAN LiZhong; WANG Jie (Jixie qiangdu)
The response surface model simulation experiment method is proposed on the basis of the influence of the dynamic characteristics of the structure on the comprehensive performance and the low efficiency of the engineering optimization design. By combining the ideas of the optimal design of space filling and Kriging interpolation to construct the initial agent model for optimal design of mechanical structure,and by using experimental design method,the error is bigger regional encrypted local encryption processing optimization,the approximate optimal solution and iteration of ideas,both inside and outside layer updating is established both in local and global space with high approximation accuracy of Kriging model. On this basis,Pareto optimal solution of the objective function is obtained based on the filter optimization algorithm and the multi-objective genetic algorithm.Finally,an example is given to demonstrate the effectiveness of the method.